The Achievement of Memorizing Al-Qur’an Among Students at Sekolah Berasrama Penuh (SBP) in Implementing the Tahfiz Model Ulul Albab (TMUA) - Ibrahim, Mohamed Akhiruddin (Advances in Social Sciences Research Journal, 2023)
The implementation of Tahfiz Model Ulul Albab (TMUA) program is an effort of Ministry of Education in expanding tahfiz education, which has an increasing demand for admission among parents every year. After ten years of the program implementation since 2014, there were still many problems and issues arose such as the level of students’ achievement in memorizing Al-Qur’an is still not yet satisfactory. Past research findings show that not all TMUA students able to complete the Al-Qur’an memorization of 30 juzuk within five years of study as outlined by the Ministry of Education. Hence, this study aims to see the achievement of Al-Qur’an memorization among Sekolah Berasrama Penuh students in the period of five months. The percentage of students’ achievement records were taken starting from school opening in March until August 2023 to examine the level of students’ achievement in completing their Al-Qur’an memorization based on prescribed syllabus. The findings show that all the SBP schools have achieved more than 50% of students who were able to complete the Al-Qur’an memorization target within the set time, however the number of students that unable to reach the prescribed syllabus are still high and not yet satisfactory.